Uitverkoren en uitgelezen : een uitgave in het kader van de Homo Literaire Manifestatie, 24 juni 1989. - Dekker, Elsbeth; Happé, Inge; van der Laak, Henk ([S.l.] : [s.n.], 1989)
Fonds Suzan Daniel (FSD)
Nederlands
Monografie